Removal of microcystin-LR using UV-assisted advanced oxidation processes and optimization of photo-Fenton-like process for treating Nak-Dong River water, South Korea - Park, Jeong-Ann; Yang, Boram; Kim, Jae-Hyun; Choi, Jae-Woo; Park, Hee-Deung; Lee, Sang-Hyup (ELSEVIER SCIENCE SA, 2018)
UV-assisted advanced oxidation processes (AOPs) are promising for the removal of microcystin-LR (MC-LR), one of cyanotoxins released during harmful algal blooms. Nevertheless, the efficiency and potential of the photo-Fenton-like process (UV-C/Fe(III)/H2O2) in treating MC-LR have not been explored in much detail. In this study, MC-LR degradation efficiencies of various UV-assisted AOPs were compared that they were higher in the order: UV-C/Fe(III)/H2O2 > UV-C/Fe(II)/H2O2 > UV-A/TiO2 > UV-C/H2O2 > UV-C > UV-A/Fe(II)/H2O2 > UVA/H2O2 > UV-A. The concentrations of Fe(III) and H2O2 used in the photo-Fenton-like process were varied to evaluate their influences on MC-LR degradation in both deionized water and a water sample from Nak-Dong River, Daegu (South Korea). The highest removal efficiency (>80%) for MC-LR was achieved after 15 min by the photo-Fenton process at a low optimum Fenton reagent concentration (Fe = 0.5 mg L-1 and H2O2 = 1 mg L-1) in the river water. Twelve transformation products of MC-LR were identified with 1029.5, 1012.5, 1015.5, 1011.5, 965.6, 835.5, 815.4 and 783.4 m/z (two products) with the presence of four reaction sites: the conjugated diene bond of Adda, the methoxy group of Adda, the C=C bond of Mdha, and the acid group of MeAsP. Theses alleviated the hepatotoxicity of MC-LR, as indicated by a protein phosphatase (PP) 2A assay. Considering the impacts of the chemistry for the treatment of river water, natural organic matter has a slightly higher impact on MC-LR degradation than the initial pH and alkalinity. The kMC-LR were maintained at 0.167-0.187 min(-1) and t(1/2) (min), obtained from the different river water samples, were all within 5 min in spite of the relatively high dissolved organic carbon concentrations.